Description of immature stages of three species of American Cetoniinae (Coleoptera: Scarabaeidae: Cetoniinae) - Orozco, Jesus; Pardo-Locarno, Luis Carlos (Zootaxa, 2004)
The larvae and pupae of three Cetoniinae scarab beetles, Gymnetis pantherina Blanchard, 1837; Gymnetis holosericea (Voet, 1779), and Euphoria precaria Janson, 1881 from Colombia are described. Multiple color patterns of adults and key larval characters are illustrated for each species for the first time. The described larvae of Gymnetis MacLeay are included in a key to the larvae of the genus, now with five species; and Euphoria precaria is added to the extant key of the known Euphoria larvae. New distributional records for the country are presented and some comments on the biology of the species in captivity are provided.Se describe la larva y la pupa de tres escarabajos cetoninos: Gymnetis pantherina Blanchard, 1837; Gymnetis holosericea (Voet, 1779), y Euphoria precaria Janson, 1881 de Colombia. Los caracteres larvales estudiados y las multiples formas de coloraci n de los adultos de las especies tratadas son ilustrados por primera vez. Una clave para las larvas de las especies de Gymnetis descritas al momento es elaborada y la clave existente para las larvas de Euphoria es actualizada con la nueva informaci n. El rango distribucional de las especies en Colombia es ampliado con nuevos registros y se presenta informaci n sobre la biolog a de las especies en cautiverio.